Pratique # 26 : Accès santé jeunesse Péninsule acadienne (ASJPA) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (2025)

Pratique # 25 : Accès éQUITÉ : Simplifier l’accès aux services de santé en français (Société Santé en français) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (2025)

Pratique # 19 : Les outils de rappel du Réseau de santé Horizon (Nouveau-Brunswick) - Benoît, Josée; Dagnogo, Djenaba Sarah; Savard, Jacinthe; Savard, Sébastien (2021)

Pratique # 27 : Accueil centralisé (Centre francophone du Grand Toronto, Ontario) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (2025)

Pratique # 18 : Le plan de contingence du Réseau de santé Horizon (Nouveau-Brunswick) - Benoît, Josée; Dagnogo, Djenaba Sarah; Savard, Jacinthe; Savard, Sébastien (2021)

A self-assessment tool for healthcare and social service provision in French: What use for managers? - Savard, Sébastien; Savard, Jacinthe; van Kemenade, Solange; Benoît, Josée; Tabor, Michelle (Healthcare Management Forum, 2020)
Language is an important determinant of health, and lack of access to quality, linguistically adapted healthcare and social services negatively impacts users. Besides the lack of bilingual resources, our previous research on Francophone minority community seniors’ trajectories through these services shed light on important and nonobvious challenges currently faced by organizations offering healthcare and social services to this population. Current service provision appeared limited due to organizations working in silos with suboptimally used resources for integrating active offer of French language services throughout the continuum of care. This situation led our team to create the Organizational and Community Resources Self-Assessment Tool for Active Offer and Continuity of French Language Healthcare and Social Services, which is intended to help managers and service providers promote and facilitate the integration of active offer throughout the continuum of service provision. This article describes the Tool’s creation, content validation, and pilot-testing.

Structural facilitators and barriers to access to and continuity of French-language healthcare and social services in Ontario’s Champlain region - Savard, Jacinthe; Bigney, Kte; Kubina, Lucy-Ann; Savard, Sébastien; Drolet, Marie (Healthcare Policy, 2020)
Purpose: The purpose of this article is to examine access to and continuity of French-language healthcare and social services in Ontario's Champlain region through an analytical framework that incorporates people seeking care, their caregivers and the linguistic component of care into a health and social service system bounded by community, organizational, political and symbolic structures. Methods: Experiences of French-speaking seniors seeking care and those of health and social service providers and managers from two qualitative exploratory studies are used to describe trajectories through the system. Results: Participants exposed how, together with community vitality, issues within each of the system's symbolic, political or regulatory and organizational structures influence these trajectories. Conclusions: To meet the needs of francophone seniors, additional work is needed to increase French-language services coordination within the organizational, regulatory and policy structures of the health and social service system.

Management strategies to improve French language service coordination and continuity for official language Francophone seniors in Canada - de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette; Kubina, Lucy-Ann (Healthcare Management Forum, 2020)
Evidence suggests that language barriers present obstacles to healthcare access and quality for Francophone seniors in official language minority communities across Canada. Addressing language barriers and providing continuity is challenging, as French language services (FLSs) rely heavily on bilingual providers and the practice of active offer by all staff. This qualitative research used semi-structured group and individual interviews to explore mechanisms supporting FLS coordination and continuity in two Canadian provinces. Identification of the language variable in health records, virtual healthcare, and FLS directories are conducive to FLS continuity, but financial and resource limitations present major obstacles. Management strategies to facilitate continuity of FLS across health organizations are discussed.

L’accès aux services en français, de la connaissance des défis à l’accompagnement des organisations vers le changement. - Savard, Sébastien; Savard, Jacinthe; Sauvé-Schenk, Katrine; van Kemenade, Solange; Benoît, Josée (Minorités linguistiques et société, 2024)
Depuis 2011, le Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (GReFoPS) cherche à mieux comprendre les facilitateurs et les obstacles à l’offre de services en français dans un contexte linguistique minoritaire au Canada. Dans cet article, les auteurs présentent un bilan de près de 12 ans de recherche sur le sujet, en décrivant les facteurs individuels et organisationnels qui influencent l’offre de services en français. Les résultats de ces études ont mis en lumière quelques mécanismes organisationnels ou interorganisationnels qui ont permis l’émergence de pratiques novatrices pour améliorer l’offre de services en français dans les services communautaires et institutionnels. On y décrit également des outils créés pour aider les gestionnaires de ces services à identifier des mesures et des mécanismes pouvant répondre aux besoins des usagers francophones en situation minoritaire. Mots-clés : accès, services sociaux et de santé, francophones, contexte minoritaire, Canada

Strategies to improve French language health and social service continuity for seniors in Ontario and Manitoba - Savard, Jacinthe; Savard, Sébastien; de Moissac, Danielle; Giasson, Florette; Kubina, Lucy-Ann (Linguistic Minorities and Society, 2021)
Access to health and social services in one’s official language of choice is an important component of quality and safety of care for seniors. Access can be fragmented, even in the context of legislation guaranteeing the right to receive such services, and in areas with a higher proportion of bilingual providers. Using a community-based participatory approach, we identified mechanisms promoting or impeding the clinical integration of health and social French language services intended for seniors living in two Canadian Francophone minority communities. Thirteen recommendations highlight the possibility for new initiatives to promote a continuum of French language health and social services in a minority context, involving collaboration among a variety of actors at all levels of our analytical framework: service trajectory (providers); francophone communities; organizational; political and regulatory; and symbolic (values) structures. Keywords: seniors, linguistic minorities, service integration, health and social services, continuity of care

Pratiques novatrices en santé mentale pour les populations de langue officielle minoritaire à Terre-Neuve-et-Labrador et dans les Territoires du Nord-Ouest - van Kemenade, Solange; Bouchard, Louise; Savard, Jacinthe; Savard, Sébastien; Oukouomi, G.; Michel, J. N. (Université d'Ottawa, Chaire de recherche de l’Université d’Ottawa et de l’Institut du Savoir Montfort sur la santé des francophones de l’Ontario et Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2021)

Vers de nouvelles approches en santé mentale : possibilités et limites pour les francophones en situation minoritaire à Terre-Neuve-et-Labrador et aux Territoires du Nord-Ouest - Savard, Sébastien; van Kemenade, Solange; Bouchard, Louise; Savard, Jacinthe; Oukouami D, Ghisleine; Michel, Jean Nephetaly (Canadian Social Work Review / Revue canadienne de service social, 2024)
De nouvelles approches axées sur la cybersanté mentale l’aide à la navigation du système, les cliniques sans rendez-vous, ainsi que les approches plus traditionnelles comme les lignes d’aide et de crise cohabitent afin de promouvoir ou d’intervenir précocement en santé mentale. Comment ces interventions répondent-elles aux besoins des francophones en contexte linguistique minoritaire alors que la communication est au coeur d’une consultation réussie? Objectif : Documenter six initiatives à Terre-Neuve-et-Labrador et dans les Territoires du Nord-Ouest. Méthode : Études de cas, incluant trente-six entrevues semi-dirigées auprès des autorités sanitaires, des fournisseurs de soins et des usagers. Résultats : La gratuité, l’anonymat, la rapidité, la présence des pairs travailleurs, l’absence de jugement et des démarches simples facilitent l’accès aux programmes. Parmi les limites, l’insuffisance de services en français et l’accent sur les thérapies brèves peuvent affecter la continuité des services, notamment pour les usagers francophones. Conclusion : Malgré les efforts pour améliorer l’offre de services en santé mentale aux francophones, des lacunes subsistent. L’article présente certaines stratégies qui permettraient d’améliorer l’offre de ces services. Mots-clés : Santé mentale, cybersanté mentale, initiatives novatrices, Terre-Neuve-et-Labrador, Territoires du Nord-Ouest, soins par paliers, francophones en situation minoritaire

Active offer of services in Canada’s official languages: development of a patient experience questionnaire - Sauvé-Schenk, Katrine; Pignac, Sarah; Kemenade, Solange Van; Savard, Sébastien; Prud'homme, Denis; Savard, Jacinthe (Journal of Communication in Healthcare, 2026)
ABSTRACT Background: In the bilingual Canadian context, the use of a preferred official language with healthcare providers is linked to optimized communication, respectful patient-centered care, improved safety and quality of services. This study aimed to develop and test a questionnaire that measures patients’ experience of how language was considered during an outpatient health encounter. Methods: French and English questions were drafted based on a literature review. Questionnaire content and flow were validated through focus groups with experts and service users. Question understanding and clarity was verified with cognitive interviews and pre-tests with diverse service users. The final questionnaire was pilot tested in three health organizations and temporal stability, and construct validity was verified. Results: Participants were nine anglophone and eleven francophone experts and service users for the focus groups, six anglophone and six francophone service users for the cognitive interviews, eleven anglophone and ten francophone service users for the pre-test. The resulting questionnaire has 31 experience-related questions organized under six themes: arrival/greeting, interpretation and translation services, language of health services, relationship with healthcare providers, visibility of official languages and follow-up. The questionnaire is completed online in French or English. The questionnaire was pilot tested with 199 participants in three sites. Temporal stability was moderate to good. Initial evidence of construct validity was demonstrated, suggesting that the questionnaire is adequate to evaluate patient experience. Conclusion: This questionnaire is the first known bilingual patient-experience tool, focused on the active offer of services in official languages during outpatient healthcare encounters, with preliminary validation.

Pratique # 12 : Les Lunchs-causeries au Centre de services communautaires Vanier (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 10 : Les points de service satellites (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 11 : The Information and Support Guide for Caregivers (Québec) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Practice # 3: The Pavillon Omer Deslauriers: A Francophone Unit at Bendale Acres (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 13 : Une infirmière de Santé publique dans un centre de services communautaires qui assure l’aiguillage des aînés (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 14 : Les Foires d’information de la Fédération des aînés et des retraités francophones de l’Ontario (FARFO) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Implementation of Innovative Strategies to Increase French Language Services in Three Canadian Health and Social Services Organizations. Research report, - Savard, Sébastien; Savard, Jacinthe; Benoît, Josée; Sauvé-Schenk, Katrine; de Moissac, Danielle; Durand, François; Dupuis-Blanchard, Suzanne (2024)

Évaluation de la mise en œuvre de services en français en contexte minoritaire : développement d’un questionnaire sur l’expérience des usagers - Sauvé-Schenk, K; Savard, Jacinthe; Savard, Sébastien; Prud’homme, Denis; van Kemenade, Solange; Le Callonnec, L; Pignac, S (2022)

Prolonged Impact of the COVID-19 Pandemic on the Well-being and Roles of Family/Friend Caregivers of Older Adults Living at Home in Canadian Official Language Minority or Majority Communities - Savard, Jacinthe; Savard, Sébastien; Duong, Patrick; Hatungimana, Nelly Oriane; Benoit, Josée; De Moissac, Danielle; Dupuis-Blanchard, Suzanne; Robitaille, Annie (Canadian Journal on Aging / La Revue canadienne du vieillissement, 2026)